Differential effects of positive versus negative contact: The importance of distinguishing valence from intensity - Schäfer, Sarina J.; Kros, Mathijs; Hewstone, Miles; Schmid, Katharina; Fell, Benjamin F.; Jaspers, Eva; Kauff, Mathias; Lemmer, Gunnar; Christ, Oliver (Group processes & intergroup relations, 2025)
More and more research is considering the effects of both positive and negative intergroup contact on intergroup attitudes. To date, little is known about what factors may differentially influence these effects. We propose that differentiating not only between positive and negative contact (i.e., its valence), but also considering the intensity (i.e., low or high positivity/negativity) of contact valence is critical to understanding contact effects. We predicted that intensifying positivity in the realm of positive contact would have a stronger effect on outgroup attitudes than intensifying negativity. We report evidence supporting this hypothesis from three experiments which manipulated the quality of feedback given during a cooperation task by a confederate who acted as a member of a student outgroup (two online: N = 87, N = 169; one in person: N = 78), summarized in an internal meta-analysis and a large survey of White British majority and Asian British minority members (N = 2,994). Our results suggest that intensity of valenced intergroup contact may be a key factor for resolving inconsistencies in the current literature on valenced intergroup contact.